Primer registro de Atractocerus brasiliensis Lepeletier & audinet-serville (Coleoptera: lymexylidae) para Jalisco, México - Rivera-Cervantes, Luis Eugenio; García-Real, Edith; Morón, Miguel Ángel (Instituto de Ecología, A.C., 2008)
This is the first record of Atractocerus brasiliensis (Coleoptera: Lymexylidae) from Jalisco State, Mexico.